KEBOLEHAN WANITA BERKARIR DALAM PERSPEKTIF AL-QUR’AN: Studi Tafsir Al-Misbah Karya Quraish Shihab - Siti Laelatu Nafisah; Reza Fandana (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2024)
This research is motivated by various perspectives on the permissibility of women working, usually based on the interpretation of religious texts. The focus of this study is the analysis of relevant Qur'anic verses, such as Surah Al-Ahzab verse 33 and Surah An-Nahl verse 97, which indicate that Islam equally rewards righteous deeds by both men and women, particularly as interpreted in Tafsir al-Misbah and the works of contemporary scholars like Quraish Shihab. This study aims to analyze and interpret the Qur'anic exegesis regarding career women by the exegete Quraish Shihab in his tafsir Al-Misbah. The research design is a literature study, analyzing Quraish Shihab's interpretation of career women in his tafsir Al-Misbah. This research is also supported by secondary data from various documents, books, scriptures, and related research on the topic. The data collection method is documentation. The results of this study indicate that women can actively participate in various aspects of their lives without violating Islamic rules. Therefore, the role of women in social and economic development is recognized and considered part of their devotion to Allah Swt